Research on the Percolation Mechanism of Perturbation Under Simultaneous Fracturing in Shale Reservoirs - He, Jie; Niu, Xiaobing; Meng, Qingchun; Guo, Fajun; Wang, Hongmei; Liu, Yicang; Wang, Lianguo; Kang, Yongmei; Hu, Kelai; Zhu, Yushuang (Frontiers in Energy Research, 2021)
Compared with conventional reservoirs, shale gas reservoirs usually have no natural productivity or lower productivity, and the rate of production decline is high in the later stage. The production of shale gas can be effectively improved by designing reasonably or fracturing. Therefore, it is critical for shale gas reservoir to study how to design proper parameters to make it effectively developed. Based on data of block-A region of the Zhejiang gas field, considering the contribution of rock compression to the production, the productivity formula of horizontal well at different seepage stages is deduced. Data from block-A are verified by orthogonal experiment, including gas reservoir parameters and engineering parameters. The results show that the order of reservoir parameters that affect the development of shale gas is as follows: Langmuir pressure, diffusion coefficient, cross flow coefficient, and Langmuir volume; the order of engineering parameters that affect the development of shale gas is as follows: number of fractures, horizontal section length, production pressure, fractures length, row spacing, and well spacing. The research results have been applied to the Zhejiang gas field. The initial rate of decline after adjustment is reduced by 26.08% and production increases by 17.06% after stabilization compared to wells without adjustment parameters. The research has important reference significance for the efficient development of similar gas reservoirs.